Pengaruh Mekanisme Bonus, Exchange Rate, Intangible Assets, dan Kompensasi Rugi Fiskal Terhadap Keputusan Perusahaan Melakukan Transfer Pricing - Weni Avri Rahman; Charoline Cheisviyanny (Universitas Negeri Padang, 2020)
This research aims to examine to analyze the effect of bonus scheme, exchange rate, intangible assets, and fiscal loss compensation on the company’s decision to do transfer pricing. The population in this research are all of the companies listed in Indonesia Stock Exchange (IDX) in 2014 until 2018. The sample of study was determined by using purposive sampling method, and that total sample 93 companies. The data used secondary data and collected by documentation at www.idx.com. This research use logistic regression analysis as analysis method. The result of analysis in this research showed that bonus scheme, exchange rate, and fiscal loss compensation had no effect on the company’s decision to do transfer pricing. Intangible Assets had a positive effect on the company’s decision to do transfer pricing